Effect of Amplitude and Duration of Cyclic Loading on Frictional Sliding Instability in Granular Media: Implication to Earthquake Triggering of Landslides. Issue 11 (12th November 2022) - Hu, Wei; Luo, Hui; Xu, Qiang; McSaveney, Mauri; Huang, Runqiu; Zheng, Jie; Wang, Yujie; Jia, Xiaoping
Abstract: Strong earthquakes with larger magnitude and longer durations trigger many landslides, however, how magnitude and duration affect landslides is still unclear. Many factors could contribute to this, including additional shear stress provided by strong ground motion, or "seismogenic liquefaction"; herein, we hypothesize that the dynamic weakening of sliding zone gouge is important. We explored the influence of earthquake magnitude and duration on landslide triggering by simulating the seismic response of sliding zone gouge using a dynamic ring‐shear device and glass spheres. The experiments showed that vibration with larger amplitudes and longer durations more easily trigger deformation and even instability in dry granular materials. We used a dynamic triaxial‐bender system to find that the shear modulus of these materials decreased with the increase in duration and amplitude of cyclic loading. We suggest that this universal decrease in shear modulus is an important landslide‐trigger mechanism. Our results revealed how magnitude and duration of earthquakes affect co‐seismic landslides and why earthquakes with larger magnitude and long durations can trigger more co‐seismic landslides. Plain Language Summary: Strong earthquakes with larger magnitudes and longer durations trigger many landslides. Some mechanisms have been proposed to explain the triggering, for example, seismic waves provide additional driving force which increases the shear stress on the sliding plane. Earthquakes may cause an increase of pore pressure, which reduces the effective normal stress on the sliding plane. However, the mechanisms that apply to wet and dry conditions are not fully understood. We hypothesize that the dynamic weakening of sliding zone gouge caused by earthquakes is an important mechanism. We used a dynamic ring shear device and glass spheres to simulate the seismic response of sliding zone gouge, and our experiments show that larger amplitudes and longer durations more easily trigger deformation and even instability. Using a dynamic triaxial‐bender system, we found that the shear modulus decreased with the increase in duration and amplitude of vibration. Our results reveal how earthquakes with larger magnitudes and long durations trigger more co‐seismic landslides. Our experimental method may be helpful for monitoring and early warning of earthquake‐triggered landslides in the future. Key Points: Dynamic ring shear tests show the deformation characteristics of granular materials under vibration Longer durations and larger amplitudes of vibration are more likely to trigger slip and shear modulus weakening The reduction and recovery of shear modulus is an important mechanism for triggering failure of earthquake‐triggered landslides